Perancangan Desain Kalender Tahun 2024 Untuk Kementerian Agama Republik Indonesia - bastian, Hendri; Bayu Setiawan (SENIMAN: Jurnal Publikasi Desain Komunikasi Visual, 2024)
Abstract. We can't let go of the name of the calendar, of course most homes or work spaces need a calendar. The calendar is not only limited as a reminder of the time, nowadays the promotional media also utilizes various media to improve marketing efficiency, so the Calendar now has a dual function, besides the time indicator can also function as a promotional medium, Therefore many Companies and institutions want to create their own calendars, One of them is the Ministry of Religion RI, Through the branding company PT. established partners noble, this journal discusses Calendar Design on the Design Design of Calendar 2024 For the ministry of religion of the Republic of Indonesia, this design uses a qualitative method based on interviews and literature studies, through the said process resulted in the design of the Calender 2024 Ministry of Religion. Keywords: Calendar, Promotional Media, Ministry of Religion Abstrak. Kita tidak bisa lepas dari namanya kalender, tentunya Sebagian besar rumah atau ruang kerja membutuhkan kalender, kalender bukan hanya terbatas sebagai pengingat mengenai waktu, saat ini media promosi juga memanfaatkan berbagai media untuk meningkatkan efisiensi marketing, karena itu Kalender sekarang mempunyai fungsi ganda, selain petunjuk waktu dapat difungsikan juga sebagai media promosi, Oleh karena itu banyak Perusahaan dan Lembaga yang ingin membuat kalender mereka sendiri, Salah satunya Adalah Kementerian Agama RI, Melalui Perusahaan branding PT. mitra mapan mulia, Jurnal ini Membahas Mengenai Desain Kalender Pada Perancangan Desain Kalender Tahun 2024 Untuk Kementerian Agama Republik Indonesia, Perancangan ini menggunakan Metode Kualitatif yang berdasar pada wawancara dan studi literatur, Melalui Proses Tersebut dihasilkan desain Kalender 2024 Kementerian Agama.